2022
DOI: 10.1186/s13048-022-01028-7
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of angiogenesis inhibitors for recurrent ovarian cancer: a meta‑analysis

Abstract: Objective To investigate the efficacy and safety of angiogenesis inhibitors in the treatment of recurrent ovarian cancer (OC). Methods Electronic databases including PubMed, Web of Science, and the Cochrane Library were searched to find eligible studies until August 10, 2021. The data on overall survival (OS), progression-free survival (PFS), and objective response rate (ORR) were pooled. Furthermore, grade ≥ 3 adverse events (AEs) were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The Hall et al, 2020 [ 103 ] study was not included due to the fact that cyclophosphamide was used as a treatment line rather than carboplatin/paclitaxel—the superiority of combination carboplatin–paclitaxel over the cisplatin–cyclophosphamide combination was demonstrated by a previous trial [ 22 ], and the usage of cyclophosphamide may falsely alter the PFS results in favor of anti-angiogenetic drugs. The most recent meta-analysis on the subject of inhibitors of angiogenesis in ovarian-tumor patients we came across is the one performed by Zhang et al [ 104 ], referring only to recurrent ovarian tumors and containing 13 RTCs, which were all included in our study. The results of the Zhang et al meta-analysis had similar results to ours, indicating both an OS and a PFS benefit of anti-angiogenetic drugs in recurrent neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The Hall et al, 2020 [ 103 ] study was not included due to the fact that cyclophosphamide was used as a treatment line rather than carboplatin/paclitaxel—the superiority of combination carboplatin–paclitaxel over the cisplatin–cyclophosphamide combination was demonstrated by a previous trial [ 22 ], and the usage of cyclophosphamide may falsely alter the PFS results in favor of anti-angiogenetic drugs. The most recent meta-analysis on the subject of inhibitors of angiogenesis in ovarian-tumor patients we came across is the one performed by Zhang et al [ 104 ], referring only to recurrent ovarian tumors and containing 13 RTCs, which were all included in our study. The results of the Zhang et al meta-analysis had similar results to ours, indicating both an OS and a PFS benefit of anti-angiogenetic drugs in recurrent neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that inhibition of angiogenesis can inhibit tumor growth and metastasis ( 73 ). Thus angiogenesis has emerged as a target for cancer therapy ( 74 ).…”
Section: Natural Drugs Regulate Tumor Genesis and Development By Regu...mentioning
confidence: 99%
“…Nevertheless, debates persist regarding the OS advantage and the safety profile of these combined treatments ( Chekerov et al, 2018 ; Ray-Coquard et al, 2020 ; Pignata et al, 2021 ). Prior meta-analyses have explored the efficacy and toxicity of anti-angiogenic drugs in different subtypes of OC ( Yi et al, 2017 ; Helali et al, 2022 ; Zhang et al, 2022 ). However, there is a lack of a comprehensive meta-analysis to evaluate the effects of monotherapy or combination therapy with anti-angiogenic drugs on OC.…”
Section: Introductionmentioning
confidence: 99%